The Impact Of Art Puzzle On Preschool Children's Autonomy In Kb Hidayatul Islam Pakuniran Probolinggo - Kusuma, Jihan; Apriliya, Riska (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
This study discusses the impact of a puzzle to increase the autonomy of early childhood at KB Hidayatul Islam Probolinggo. This study aims to assist teachers in increasing children's autonomy with a puzzle. This type of research uses a quantitative research method. This research was carried out at KB Hidayatul Islam Probolinggo with all teacher and student councils as subjects. Researchers carried out observations, tests, and data analysis documentation using statistical data analysis techniques to obtain this data. The data collected was in the form of pretest and posttest scores. The results of this study indicate that puzzles done correctly can boost early childhood autonomy. It is also essential to pay attention to the processes involved in adopting puzzles to improve children's independence so they are pleased, cheerful, and always autonomous.